Examining Perceptions of Online Harassment among Constables in England and Wales - Bossler, Adam (2019)
The ubiquity of the Internet and computer technology has enabled individuals to engage in bullying, threats, and harassing communications online. Limited research has found that local line officers may not view these offenses as serious compared to real world crimes despite their negative physical and emotional impact on victims. The perceptions of officers can produce poor interactions with victims during calls for service, particularly victim blaming, which can reduce citizens’ confidence in police agencies generally. However, local law enforcement agencies are increasingly mandated to respond to these cases, calling to question how their views may impact the community. This study examined the attitudinal and demographic factors associated with the negative views of online harassment and bullying within a sample of 1,348 constables from 34 local agencies across England and Wales. The study found that constables with negative views toward cybercrimes and worked in agencies with inconsistent messaging related to online crimes were more likely to view online harassment as less serious and believe that these offenses could be avoided by victims. The implications of this study for local police staff and command are discussed in detail